3 2 + 1 1 + 4 2 + 2 1 + 5 2 + 3 1 + ⋯ + ( n + 2 ) 2 + n 1 + ⋯ = ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
The sum is n = 1 ∑ ∞ ( n + 2 ) 2 + n 1 , or n = 1 ∑ ∞ n 2 + 5 n + 4 1 . Note that n 2 + 5 n + 4 = ( n + 1 ) ( n + 4 ) , we could use the method of partial fractions in order to find that n 2 + 5 n + 4 1 = 3 1 ( n + 1 1 − n + 4 1 ) , so
n = 1 ∑ ∞ n 2 + 5 n + 4 1 = 3 1 n = 1 ∑ ∞ ( n + 1 1 − n + 4 1 ) = 3 1 ( 2 1 − 5 1 + 3 1 − 6 1 + 4 1 − 7 1 + 5 1 − 8 1 + 6 1 − 9 1 + … )
Some of the terms cancel, leaving only 3 1 ( 2 1 + 3 1 + 4 1 ) = 3 6 1 3
Problem Loading...
Note Loading...
Set Loading...
Assume that it is an infinite sum.
k = 1 ∑ ∞ ( k + 2 ) 2 + k 1 = k = 1 ∑ ∞ k 2 + 5 k + 4 1 = k = 1 ∑ ∞ ( k + 1 ) ( k + 4 ) 1 = 3 1 k = 1 ∑ ∞ ( k + 1 ) ( k + 4 ) 3
= 3 1 k = 1 ∑ ∞ ( k + 1 ) ( k + 4 ) ( k + 4 ) − ( k + 1 ) = 3 1 ( k = 1 ∑ ∞ ( k + 1 ) 1 − k = 1 ∑ ∞ ( k + 4 ) 1 )
= 3 1 ⋅ ( 2 1 + 3 1 + 4 1 ) = 3 6 1 3